2017
DOI: 10.4236/ajps.2017.84057
|View full text |Cite
|
Sign up to set email alerts
|

Do Plants Have a Choice of Traits to Be Modulated? Evidence from an Invasive Plant <i>Mikania micrantha</i> Kunth in Different Urban Environments

Abstract: The successful establishment of an invasive plant in a novel environment has been attributed to the phenotypic plasticity of plant traits, with most studies focussing on vegetative trait plasticity in either experimental and/or natural habitat conditions. This study explores the role of phenotypic plasticity, in both vegetative and reproductive traits, of an invasive plant Mikania micrantha growing as a ground cover in diverse urban areas in the city of Kolkata, India. Quadrat based plant and soil sampling was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…1; Franzetti et al ., 2020; Khanolkar et al ., 2020). Native weeds are integral to ecological succession, depending on the succession stage and the characteristics of the weed species involved (Banerjee et al ., 2017). For example, Epilobium angustifolium and Chamerion angustifolium rapidly colonise bare ground during ecological succession after wildfires, providing an important food source and habitat for pollinators; their rapid growth helps prevent soil erosion and facilitates woody plant regeneration (De Vitis et al ., 2022).…”
Section: Native Weed Communities Their Roles In Ecological Succession...mentioning
confidence: 99%
See 1 more Smart Citation
“…1; Franzetti et al ., 2020; Khanolkar et al ., 2020). Native weeds are integral to ecological succession, depending on the succession stage and the characteristics of the weed species involved (Banerjee et al ., 2017). For example, Epilobium angustifolium and Chamerion angustifolium rapidly colonise bare ground during ecological succession after wildfires, providing an important food source and habitat for pollinators; their rapid growth helps prevent soil erosion and facilitates woody plant regeneration (De Vitis et al ., 2022).…”
Section: Native Weed Communities Their Roles In Ecological Succession...mentioning
confidence: 99%
“…plant communities or ecosystems composed of weed species that are indigenous or native to a particular region or habitat (Wang et al ., 2022 c ), in disturbed environments may possess traits and adaptations that enable them to resist invasions by non‐native species (Divíšek et al ., 2018; Meyer et al ., 2021). These traits include rapid germination, high seed production, phenotypic plasticity, tolerance to pollutants, and efficient resource utilisation (Banerjee, Ghosh & Dewanji, 2017; Vilela et al ., 2018). While several studies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The micronutrients viz., iron, manganese, zinc and copper were estimated by using Atomic Absorption Spectrometer (AEI -5310). 23…”
Section: Micro Nutrient Analysismentioning
confidence: 99%
“…The shift of the realized climatic niche of M. micrantha toward cold and dry conditions in its invasive range is not surprising since the bioclimatic variables related to cold temperature (Bio6, Bio11) and temperature of the dry months (Bio9) made significant contributions in governing the distribution of this species. Previous studies have revealed that M. micrantha can establish across a range of environmental conditions due to phenotypic variation of physiological traits (Banerjee et al, 2017a). For example, experimental studies have found enhanced NAC gene expression in response to cold stress (Li et al, 2012) and phenotypic plasticity in traits in different altitudinal gradient (Prabu et al, 2014), to elevated CO 2 concentration (Song et al, 2009), and to contrasting light and soil water conditions (Zhang and Wen, 2009) in M. micrantha.…”
Section: Assessing Spread Dynamicsmentioning
confidence: 99%
“…Previous ENM studies have predicted the potential distribution of M. micrantha at regional (Choudhury et al, 2016), national (Iyer et al, 2019), and global (Day et al, 2016) scales, however, with the assumption of climatic niche conservatism between its native and invasive ranges. M. micrantha can establish across different environmental conditions due to its ability to express phenotypic variation of traits [e.g., photosynthetic activity (Prabu et al, 2014), water and nitrogen use efficiency (Deng et al, 2004), leaf construction cost (Song et al, 2007), and vegetative and sexual reproduction Li et al, 2013;Banerjee et al, 2017a]. In this context, the modeled distribution based on the niche conservatism hypothesis may not reflect the true potential distribution of the species.…”
Section: Introductionmentioning
confidence: 99%